Lagoa de lemnáceas empregada no pós tratamento do efluente de um wetland construido de fluxo horizontal - Maranzatto Junior, Antonio Roberto (2017)
Removing nutrients from sanitary sewage is still a major challenge. Conventional sewage treatment systems do not attenuate the high load of nutrients such as nitrogen (N) and phosphorus (P), and the usual methods of removal require high investment for installation and operation. Dumping at high concentrations in water bodies causes serious consequences such as eutrophication and, in groundwater, concern is with nitrate, which contaminates drinking water and can cause public health problems such as blue baby syndrome (methemoglobinemia). The objective of this study was to evaluate the efficiency of nutrient removal in an experimental lagoon of Lemnas (Landoltia punctata), on a bench scale, as a post-treatment unit of sanitary sewage coupled to a Horizontal Flow Built Wetland. The effluent used came from a University Restaurant. The total removal efficiency of KTN and ammoniacal nitrogen (NH4 +) was 77.27% and 56.22%, respectively, whereas in the Lemnas lagoon the removal was 48.79% and 37.67%. The average efficiency of COD removal was 86.19% and 31.87%. From the results it was possible to verify that the association of the Lemnas lagoon was shown as a viable alternative to compose the constructed Wetland System considered.